Evaluation the Efficacy of Nutritional Interventions in the Recovery and Management of Post-Concussion - Wang, Xiaoqi (Simen Owen Academic Proceedings Series, 2025)
Post-concussion syndrome (PCS) affects a substantial number of patients, often involves prolonged symptom duration, and imposes a considerable medical and economic burden. This study systematically evaluated the efficacy of nutritional interventions for PCS recovery compared to conventional treatments. Following PRISMA guidelines, a literature review identified nine studies that met inclusion criteria, examining the effects of interventions including melatonin, Enzogenol, MLC901, phytocannabinoids, and the ketogenic diet. Key findings indicated that melatonin improved sleep quality and alleviated PCS symptoms, MLC901 enhanced attention and executive functioning, Enzogenol reduced mental fatigue and promoted restorative sleep, a ketogenic diet improved visual memory, and phytocannabinoids mitigated autonomic dysfunction and related symptoms. Despite variability in study designs and limited sample sizes, nutritional interventions demonstrated promising benefits for PCS symptom management. Future research should prioritize large-scale, well-controlled trials with standardized protocols and long-term follow-up to validate these findings and inform clinical practice.